Abdominal Wall Reconstruction in Abdominal Wall Endometriosis: A Case Report and Literature Review - van Varsseveld, Otis C.; Koeijers, Gustavo G.; Rodriguez Vitoria, Juan M.; Gomes Bravio, Igor (Archives of Plastic Surgery, 2025)
Abdominal wall endometriosis (AWE) is a rare condition representing 1% of patients operated for endometriosis. We describe a case of a 26-year-old woman, with a history of cesarean delivery, who presented with cyclical pain and a subcutaneous mass in the lower abdomen. Where most AWE lesions may be surgically managed by a single surgeon, imaging revealed an unusually large lesion (13 × 4 × 10 cm) involving the rectus abdominis muscle. Plastic, gynecologic, and general surgeons combined their expertise to conduct AWE excision combined with miniabdominoplasty in a single procedure. After resection, a retrorectus mesh (Rives–Stoppa technique) reinforced the primarily closed posterior rectus sheath and an inlay mesh bridged the defect left in the anterior rectus sheath. The patient was discharged 3 days postoperatively, had minimal pain complaints, and was satisfied with cosmetic results at 1-month and later follow ups. One year postoperatively, she gave uncomplicated vaginal birth. We conclude that, in select cases, management of a large, symptomatic AWE may benefit from a multidisciplinary approach, where symptom relief and an aesthetically pleasing result for the patient can be achieved in a single procedure. We distinctively describe double mesh repair as a viable consideration for reconstruction in AWE and review current considerations in mesh repair of the abdominal wall. Further studies into this topic are warranted.
Keywords: surgery; plastic; abdominoplasty; endometriosis; surgical mesh; abdominal wall